Microstructure development in mechanically alloyed yttria dispersed austenitic steels - Phaniraj, M. P.; Kim, Dong-Ik; Shim, Jae-Hyeok; Cho, Young Whan (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Austenitic oxide dispersion strengthened (ODS) alloys containing 0.5 and 5 wt.% yttria were prepared from elemental powders (Fe-20% Ni-14%, Cr-2.5%) Mo-2.5% Al-2% Mn) by mechanical alloying. The powders were analyzed using X-ray diffraction (XRD), X-ray photoelectron spectroscopy and transmission electron microscopy (TEM), paying particular attention to the behavior of yttria. XRD and high-resolution TEM analyses show that yttria does not form a solid solution with austenite; unlike in ferritic ODS alloys, where it dissolves. Milling induces the formation of the thermodynamically favorable yttrium aluminum perovskite (YAP). Alumina from the aluminum powder in the starting blend. formed in the initial stages, of milling using oxyen available from the other elemental powders, combines with yttria to form YAP. The yttria content does riot affect alloy formation but reduces the crystallite size and strain significantly in the 5% yttria composition. TEM analysis of hot-pressed compacts reveals nanocrystalline particles of yttria, yttrium aluminium garnet and YAP. (C) 2009 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: ALUMINUM PEROVSKITE; PARTICLES; SIZE; ESCA